Pharmacokinetics, Hemostatic Efficacy, and Safety of a New Human Fibrinogen Concentrate in Adult and Pediatric Patients with Congenital Fibrinogen Deficiency - Djambas Khayat, Claudia; El-Beshlawy, Amal; Meddeb, Balkis; Khelif, Abderrahim; Miesbach, Wolfgang; Adolf, Sonia; Boehm, Heike; Aigner, Silke; Abraha, Salomon; Bohlaender, Fabian; Schuettrumpf, Joerg (Thrombosis and Haemostasis, 2025)
Congenital fibrinogen deficiencies are rare coagulopathies which are treated by fibrinogen concentrates. This trial investigated the pharmacokinetic/pharmacodynamic (PK/PD) parameters, and surrogate efficacy and safety of a new human fibrinogen concentrate (HFC), BT524, in patients with congenital afibrinogenemia or severe hypofibrinogenemia.This prospective, multi-national, open-label, single-arm PK/PD trial evaluated PK/PD parameters of HFC (part 1; phase I) and HFC as on-demand treatment or prophylaxis for bleeding events (part 2; phase III). In part 1, patients received a single-dose of HFC (70 mg/kg body weight [BW]). PK/PD parameters were calculated using a PK/PD model and non-compartmental analysis. Fibrinogen antigen (FiAg) levels were determined over 14 days by immunonephelometry and fibrinogen activity (FiAc) by Clauss assay. The efficacy variable was mean change in maximum clot firmness (MCF) analyzed by thromboelastometry. Safety parameters were evaluated for 49 days.A total of 27 patients (n = 15 adults, n = 12 children) were treated with HFC. For FiAg, mean (SD) PK parameters were: Cmax 1.81 (0.42) g/L, AUC0-∞ 173 (45.4) g*h/L, and t1/2 67.9 (15.3) h. For FiAc, they were Cmax 1.26 (0.4) g/L, AUC0-∞ 104 (33.5) g*h/L, and t1/2 60.3 (13.3) h. In adults, MCF significantly increased 1 h after HFC infusion (11.1 (5.1) mm; P < 0.0001; 95% CI: 9.33–14.47). In pediatrics, mean increase in range was 9.3 to 16.5 mm. Treatment-related adverse events were rare, with one mild increase in fibrin D-dimer. No thromboembolic events, hypersensitivity, or allergic reactions were observed.HFC effectively increased FiAg levels and FiAc, improved clot firmness, and showed a favorable safety and tolerability profile in adult and pediatric patients with congenital fibrinogen deficiency.
Keywords: afibrinogenemia; hypofibrinogenemia; congenital fibrinogen deficiency; fibrinogen concentrate; pharmacokinetics